The Accountability in the Justice System: Have Times Really Changed? Reflections From an Italian Social Reporting Experience. (4th March 2022) - Ricci, Paolo; Pavone, Pietro
Abstract : Society has not only a right to know: in contemporary democracies, there is also a right to participate in the life of public institutions. A representation of a judicial accountability aware of this is provided in this article. This research describes, by analyzing the latest social and sustainability report of the Public Prosecutor's Office of Naples, possible points of contact between reporting and citizens. The results are still not satisfactory: stakeholder engagement often remains only an appreciable attempt. However, despite gaps and uncertainties, the report goes beyond mere descriptive narrative. Innovative elements that suggest a new season for reporting in the judicial sector are present, such as the reconstruction of the economic and financial values in a prospective key, in order to arrive in the future to study the impact on society of the efficient functioning of judicial offices. Finally, this study offers some ideas for rethinking the Italian Judiciary in a sustainability key.